RANCANG BANGUN APLIKASI CERDAS (LIMBEKFEED) MENGGUNAKAN METODE PROFILE MATCHING DALAM PENENTUAN DOSIS PEMBERIAN PAKAN TERNAK IKAN LELE - Ridho, Abdurrahman; Putri, Andriani (Antivirus : Jurnal Ilmiah Teknik Informatika, 2023)
In catfish farming, providing the right feed is crucial for optimal growth and health. However, determining the accurate dosage of feed that is suitable for individual catfish can be complex and time-consuming. To address this challenge, we have developed an intelligent application called "Limbekfeed" using the Profile Matching method for determining the dosage of catfish livestock feed. The prototype of this application leverages the Profile Matching method, which connects the profile of the catfish with the feed profiles available in the database. Users input data such as size, weight, age, and water quality. The prototype application then compares this data with the predefined feed profiles in the system and provides recommendations for the most suitable feed dosage. Test results indicate that the "Limbekfeed" application prototype is expected to provide feed dosage recommendations to help farmers avoid the risks of overfeeding or underfeeding.